2005
DOI: 10.1007/s11104-004-8068-6
|View full text |Cite
|
Sign up to set email alerts
|

The use of indigenous plant species and calcium phosphate for the stabilization of highly metal-polluted sites in southern Poland

Abstract: Highly metal-polluted (Pb, Cd, Zn) soil from a non-ferrous mine and smelter site in southern Poland, further referred to as ''Waryn´ski'' soil, was used to test indigenous plant species for stabilization effectiveness of heavy metals in soils. Results of pilot investigations with commercially available cultivars of plant species showed that these cultivars could not grow on this highly polluted soil even with the application of soil amendments to stabilize the heavy metals. Based on these results, mesocosm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(31 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…A decrease in the mobility of Cd, Zn and Pb in limed soil and an effective decrease in the uptake of these elements by several crops has been investigated and confirmed in pot experiments and under field conditions (Lee et al 2004;Kucharski et al 2005;Castaldi et al 2005). In long-term field experiments (from 15 to 63 years) Gavi et al (1997) also observed a more apparent effect of soil pH on the mobility of Cd compared to N and P fertilisation.…”
Section: Discussionmentioning
confidence: 64%
“…A decrease in the mobility of Cd, Zn and Pb in limed soil and an effective decrease in the uptake of these elements by several crops has been investigated and confirmed in pot experiments and under field conditions (Lee et al 2004;Kucharski et al 2005;Castaldi et al 2005). In long-term field experiments (from 15 to 63 years) Gavi et al (1997) also observed a more apparent effect of soil pH on the mobility of Cd compared to N and P fertilisation.…”
Section: Discussionmentioning
confidence: 64%
“…The primary minerals of concern were zinc, lead and cadmium ore, dolomite, silt, and grave. The enterprise operated for 70 years, and in 1989, production was closed down, and activities toward the revitalization of 460 ha property were started (Kucharski et al 2005). The area of concern is situated in the immediate vicinity of the former smelter.…”
Section: Study Sitesmentioning
confidence: 99%
“…A loamy sandy soil collected from the 0-20 cm soil layer at the Waryński smelter site, an abandoned industrial site near Katowice located in the south-central part of Poland, was used as a source of Cd, Pb, and Zn contaminated soil (see Kucharski et al (2005) for a site description). An uncontaminated, sandy soil was sampled from the plough layer (0-25 cm) of arable land cropped with forage maize (Zea mays L.) near Sellingen located in the north of the Netherlands.…”
Section: Soilsmentioning
confidence: 99%
“…However, for soils directly affected by mine and ore processing waste, this is more difficult, because these matrices can in fact not be considered as soil, and comparable, uncontaminated matrices are difficult to find. On the other hand, these matrices are usually heavily contaminated with HMs (e.g., Kucharski et al, 2005) and less appropriate for phytoextraction, due to the very long phytoextraction duration needed to complete remediation (Robinson et al, 1998;Zhao et al, 2003).…”
Section: Estimation Of Phytoextraction Durationmentioning
confidence: 99%
See 1 more Smart Citation